Weak Cytotoxic T Cells Activation Predicts Low-Grade Dysplasia Persistence in Ulcerative Colitis. Issue 7 (July 2019) - Kotsafti, Andromachi; D'Incà, Renata; Scarpa, Melania; Fassan, Matteo; Angriman, Imerio; Mescoli, Claudia; Bortoli, Nicolò; Brun, Paola; Bardini, Romeo; Rugge, Massimo; Savarino, Edoardo; Zingone, Fabiana; et al.
Abstract : INTRODUCTION: In patients with ulcerative colitis (UC), dysplasia develops in 10%–20% of cases. The persistence of low-grade dysplasia (LGD) in UC in 2 consecutive observations is still an indication for restorative proctocolectomy. Our hypothesis is that in the case of weak cytotoxic activation, dysplasia persists. We aimed to identify possible immunological markers of LGD presence and persistence. METHODS: We prospectively enrolled 112 UC patients who underwent screening colonoscopy (T0) who had biopsies taken from their sigmoid colon. Ninety of them had at least a second colonoscopy (T1) with biopsies taken in the sigmoid colon and 8 patients had dysplasia in both examinations suggesting a persistence of LGD in their colon. Immunohistochemistry and real time polymerase chain reaction for CD4, CD69, CD107, and CD8β messenger RNA (mRNA) expression and flow cytometry for epithelial cells expressing CD80 or HLA avidin-biotin complex were performed. Non-parametric statistics, receiver operating characteristic curves analysis, and logistic multiple regression analysis were used. RESULTS: Thirteen patients had LGD diagnosed at T0. The mucosal mRNA expression of CD4, CD69, and CD8β was significantly lower than in patients without dysplasia ( P = 0.033, P = 0.046 and P = 0.007, respectively). A second colonoscopy was performed in 90 patients after a median follow-up of 17 (12–25) months and 14 of the patients were diagnosed with LGD. In these patients, CD8β mRNA expression at T0 was significantly lower in patients without dysplasia ( P = 0.004). A multivariate survival analysis in a model including CD8β mRNA levels and age >50 demonstrated that both items were independent predictors of dysplasia at follow-up (hazard ratio [HR] = 0.47 [95% confidence interval [CI]: 0.26–0.86], P = 0.014, and HR = 13.32 [95% CI: 1.72–102.92], P = 0.013). DISCUSSION: These data suggest a low cytotoxic T cell activation in the colonic mucosa of UC patients who do not manage to clear dysplasia. Thus, low level of CD8β mRNA expression in non-dysplastic colonic mucosa might be considered in future studies about the decision making of management of LGD in UC.